Sexual harassment at the university: From denial to acknowledgement and resistance - Fernández Revoredo, Marisol (2019)
In this article, I propose that sexual harassment has become part of the institutional culture at universities, however socially normalized throughout history. As a consequence of movements such as #Metoo, Notoneless (Niunamenos), No more silence (Se acabó el silencio), and others, female university students, many groups and collectives have gained strength and begun to make political demands for safer educational environments, especially against sexual harassment. This is partly possible since important regulations to stop this form of violence were set in 2018, containing obligations both for public and private universities. I suggest the adoption of regulations is insufficient in order to stop sexual harassment at higher education institutions. It is rather necessary to dismantle the gender institutional cultures that excludes women. To this end, I present the implementation to channel sexual harassment complaints at the Pontifical Catholic University of Peru (PUCP). Denial, acknowledgment and resistance describe this particular process. I propose to examine it, recognizing its achievements and weaknesses.